PERANAN LAZDAI DALAM PENGELOLAAN DANA ZAKAT UNTUK BIDANG PENDIDIKAN (Studi pada Lembaga Amil Zakat Amal Insani (LAZDAI) Lampung) - Isnawati, Isnawati; Wirawan, Bintang (SOCIOLOGIE, 2013)
This research intends to describe and explain how LAZDAI role in managing zakat funds for education and what the enabling and inhibiting factors in its management. This type of research used in this study is a qualitative data collection method of observation, documentation and in-depth interview study. The data analysis was done by data reduction, data presentation, and verification.From the results of the study showed that LAZDAI role in the management of zakat funds consist of the collection, distribution and utilization. As for the utilization realized in some programs, such as: scholarships PRO CERMAT, PAB, Back to School, RDP LSC and BOS poor. Barriers faced by lack of operational, less active recipients follow the guidance. LAZDAI supporting factors in managing zakat is the support of the donors who come to introduce LAZDAI on society, good service and programs that attract and strategic LAZDAI headquarters.Keywords: LAZDAI, manage zakat, education